SIMILARITIES OF ACCOUNTING AND STATISTICAL METHOD. - Rorem, C. R. (The Accounting Review, 1927)
Abstract Accounting and statistics, are similar in their uses, for both are used as tools of control. They are also similar in their method, bearing, so to speak, a family resemblance, for accounting and statistics may be regarded as offspring of the single parent, quantitative method of analysis. The quantitative method of analysis has been very successful in the natural sciences, because most natural phenomena can be easily segregated and measured. This method has been the basis of many of the important scientific discoveries of recent years. In fact, it has been asserted that progress in the natural sciences has always waited upon the development of adequate quantitative technique. In the social sciences also it has been maintained that adequate control can only be obtained from better quantitative treatment of the phenomena. It is, of course, often difficult to measure economic phenomena accurately, nevertheless the measurement is necessary. The business enterprise organized for private profit has accordingly developed a technique of measuring and recording it. Facts, and business policies are now formed primarily on the basis of the quantitative data available in accounting and statistical report.